Peran Badan Narkotika Nasional Propinsi DIY Dalam Pencegahan Narkoba di Kota Yogyakarta - Buton, Rafli; Hendra, Djaya (Universitas Widya Mataram, 2019)
The issue of drug abuse or drug use is still a problem that is quite concerning for the Indonesian people until now. Indonesia is the right target for drug traffickers because of its large population and a large number of young people. This is a big challenge for the government to overcome this problem, through the institution, namely the National Narcotics Agency. This research was conducted with the aim to finding out what steps have been taken by the National Narcotics Agency to overcoming the problem of drug use, especially in Yogyakarta. This research used descriptive research methods that try to obtain facts and provides an overview of events and phenomena in people's lives to describe what is currently applicable. In overcoming the problem of drug abuse, especially in Yogyakarta, the Yogyakarta Provincial National Narcotics Agency has taken several steps, including increasing knowledge, give understanding and awareness of drug use. Take preventive measures and carry out advocacy. In carrying out its duties, BNNP DIY also always collaborates with other institutions, such as government agencies, private agencies, educational institutions and the community.